Finding a Job in the 21st Century: Seek training, be flexible, and get hired in the fast-moving world of the future. - Challenger, John A. (Futurist)
Immigration, globalization, and outsourcing, among other trends affecting employment and the workplace, will evolve over the next two decades to transform the workplace completely, and well-trained and flexible employees will be at a premium. Over 5 million layoffs have been announced in the United States since the start of 2008. Economists are forecasting that U.S. unemployment may top out at 10.5 percent or over 11 percent by the middle of 2010. The writer provides advice on looking for work in the future.